2021
DOI: 10.3390/electronics10070868
|View full text |Cite
|
Sign up to set email alerts
|

Facial Emotion Recognition from an Unmanned Flying Social Robot for Home Care of Dependent People

Abstract: This work is part of an ongoing research project to develop an unmanned flying social robot to monitor dependants at home in order to detect the person’s state and bring the necessary assistance. In this sense, this paper focuses on the description of a virtual reality (VR) simulation platform for the monitoring process of an avatar in a virtual home by a rotatory-wing autonomous unmanned aerial vehicle (UAV). This platform is based on a distributed architecture composed of three modules communicated through t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 35 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…This latter robotic field in particular is rapidly progressing and benefits other relevant technologies [ 13 , 14 , 15 ]. A classification of different robots according to their embodiments is listed in Table 3 .…”
Section: Discussionmentioning
confidence: 99%
“…This latter robotic field in particular is rapidly progressing and benefits other relevant technologies [ 13 , 14 , 15 ]. A classification of different robots according to their embodiments is listed in Table 3 .…”
Section: Discussionmentioning
confidence: 99%
“…From the experiments conducted, it can be concluded that interoperability between Unity and other languages is improved in terms of data flow by using a subscribe/publish communication protocol such as MQTT rather than creating a native plugin as this is dependent on running on the same thread as Unity. MQTT had already been used by our research team in recent applications related to simulated UAV indoors (e.g., [9,39,41]). All video processing was done externally with MQTT, allowing more FPS to be processed.…”
Section: Discussionmentioning
confidence: 99%
“…MQTT has been selected in our approach as it has already shown excellent results in our previous works for MATLAB/Simulink integration [9,39]. Moreover, the combination of an external module programmed in Python for image processing and communicated via MQTT has recently been implemented to evaluate emotion recognition as part of ongoing research [40,41].…”
Section: Related Workmentioning
confidence: 99%
“…The link between the headset and the robotic platform was created using the Message Queueing Telemetry Transport (MQTT) communication protocol [ 25 ]. MQTT is a lightweight protocol for IoT messaging and is widely used in robot control systems [ 26 , 27 , 28 , 29 , 30 , 31 ]. It was our choice because it has a small computational overhead and was easy to integrate into our system.…”
Section: Methodsmentioning
confidence: 99%